Acidic Leaching Of Turkish Lateritic Nickel Ore - Fatma Arslan (The Minerals, Metals and Materials Society, 2006)
The lateritic nickel ore sample subjected to this experimental study was taken from Çalda ore deposit (Turkey) and contains 1.43% Ni and 0.105% Co. Mineralogical investigations showed that the ore sample contains asbolane, chromite, limonite, hematite, goethite, lepidocrocite, magnetite, serpentine, and clay type minerals together with chalcedon, quartz, calcite, and chlorite. In the acidic leaching experiments, the effects of temperature, acid (H2SO4) concentration, and leaching time on nickel leaching recoveries were investigated. Leaching recovery versus time curves showed a parabolic trend and increasing the temperature shifted that curves to the higher values. The dissolution of nickel from lateritic ore can be explained by a shrinking core model and the apparent activation energy was found as 47.34 kJ/mol in the range given by the literature. The highest Ni and Co leaching efficiencies as 90.2% and 96.8% respectively were obtained at 80°C temperature, 200 g/L H2SO4 concentration, and 8 hours of leaching time.